New genus of erotine net-winged beetles, Damzenium gen. nov. (Coleoptera: Lycidae), from Eocene Rovno amber - Kazantsev, Sergey V.; Bocak, Ladislav (Zootaxa, 2022)
A new genus and a new species of erotine net-winged beetles, Damzenium rivnense gen., sp. nov., are described from late Eocene Rovno amber of Ukraine. The new taxon is placed in the tribe Erotini (Lycidae: Erotinae) based on the general appearance, structure of pronotal carinae and elytral costae. Its elytral primary costa 3 is very stout and forms the humeral edge. Primary costa 4 is weak and we have not been able to clearly identify regular four rows of cells in the wide external interstice. Similar modification of elytral longitudinal costae is known from the related tribe Dictyopterini. This discovery increases the number of Baltic and Rovno amber taxa of Lycidae to six genera and seven species. Remarkably, five genera and six species of these belong in the subfamily Erotinae, which has never been reported from other amber deposits. This quite species-poor group of net-winged beetles is still represented almost exclusively in the Holarctic fauna.